Discharge Planning of STEMI Patients by Multidisciplinary Professionals to Improve the Health Services - Rahmatul Fitriyah; Nursalam Nursalam; Ita Maulidiawati (Universitas Airlangga, 2020)
Introduction: Discharge planning starts at admission and begins by determining the educational needs. The objective of this study was to explore the implementation of discharge planning held by multidisciplinary professionals for STEMI (ST elevation myocardial infarction) patients. Methods: The design of this study was descriptive and the data was collected through in-depth interviews with the participants.Results: The results of the interview were transcribed verbatim, and then a FGD (Focus Group Discussion) was conducted. The participants consisted of11 nurses, 1 nutritionist and 1 pharmacist with a minimum working period of 2-10 years. Sampling started with the purposive sampling method. Several things influence the implementation of discharge planning viewed from the perspective of multidisciplinary professionals according to productivity theory in the organization of a cooperative, namely the motivation of the health workers, the abilities and knowledge of the health workers, the job design and the work schedule involved. Conclussion: . For the future, it is necessary to have digital guideline/tools available that can be easily accessed by multidisciplinary professionals to make the work schedule for health workers optimal to improve the health services.